Indigenous Peoples in Regional Institutions: A Comparative Perspective between ASEAN and the Arctic Council - Muhammad Dwiki Mahendra (Center for Southeast Asian Social Studies (CESASS), 2021)
The study of Indigenous People is a vast subject and it is continuously growing. Indigenous Peoples often lack formal recognition over their lands, rights, and at worst, their identities hence they are often undermined by the government and international law. Such things were possible since the recognition of Indigenous Peoples is varied and depends on each national or regional perspective. Within Southeast Asia’s regional organization, the Association of Southeast Asian Nations (ASEAN), no reference to the Indigenous Peoples was made on its founding document. This paper focuses on the issue of Indigenous Peoples by comparing the position of Indigenous Peoples within the framework of ASEAN to Arctic Council. By qualitatively analyzing relevant references on ASEAN, Arctic Council, and Indigenous Peoples, this article aims to understand the stark differences of how ASEAN and Arctic Council recognize the Indigenous Peoples within each region. Such understanding is necessary to drives ASEAN and its member states to accommodate broader rights to Indigenous Peoples.